Secrecy : the American experience - Moynihan, Daniel P. (Daniel Patrick), 1927-2003. (New Haven : Yale University Press, 1998)
Senator Daniel Patrick Moynihan, chairman of the bipartisan Commission on Protecting and Reducing Government Secrecy, here presents an eloquent and fascinating account of the development of secrecy as a mode of regulation in American government since World War I - how it was born, how world events shaped it, how it has adversely affected momentous political decisions and events, and how it has eluded efforts to curtail or end it. Senator Moynihan begins with the intriguing story of the Venona project, the Soviet spy cables intercepted during World War II and decrypted by the U.S. Army - but never passed on to President Truman. The divisive Hiss perjury trial and the McCarthy era of suspicion might have had a far different impact on American society, says Moynihan, if government agencies had not kept secrets from one another as a means of shoring up their power. He discusses the Bay of Pigs, Watergate, the Iran-Contra affair, and, finally, the failure to forecast the collapse of the Soviet Union, suggesting the many of the tragedies resulting from these events could have been averted had the issues been clarified in an open exchange of ideas.
Chapter 1. Secrecy as regulation -- Chapter 2. The experience of World War I -- Chapter 3. The encounter with communism -- Chapter 4. The experience of World War II -- Chapter 5. The bomb -- Chapter 6. A culture of secrecy -- Chapter 7. The routinization of secrecy -- Chapter 8. A culture of openness.
Includes bibliographical references (pages 229-253) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Official secrets -- United States -- History -- 20th century; Executive privilege (Government information) -- United States -- History -- 20th century; Security classification (Government documents) -- United States -- History -- 20th century; Secrets d'État -- États-Unis -- Histoire -- 20e siècle.; Privilège de l'exécutif (Information sur l'État) -- États-Unis -- Histoire -- 20e siècle.; Classification de sécurité (Documents gouvernementaux) -- États-Unis -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Public Affairs & Administration; Executive privilege (Government information); Official secrets; Security classification (Government documents); United States; Geheimdokument; Spionageabwehr; Staatsgeheimnis; USA; Geheimhouding; Overheidsdocumenten; 1900-1999; History